Неканоническое спектральное разложение случайных функций тяговых напряжения и тока в системах электрического транспорта - Костин, Николай Александрович; Шейкина, Ольга Григорьевна (НТУ "ХПИ", 2015)
В статье предложено адаптированное к системам электрического транспорта неканоническое разложение случайных процессов тяговых напряжений и токов. Выполнено численное представление случайной функции напряжения на токоприемниках электровозов ВЛ8 и ДЭ1.

The paper proposes the non-canonical spectral decomposition of random functions of the traction voltages and currents. This decomposition is adapted for the electric transportation systems. The numerical representation is carried out for the random function of voltage on the pantograph of electric locomotives VL8 and DE1.
Non-canonical spectral decomposition of random functions of the traction voltage and current in electric transportation systems
Keywords: разложение величины; мотор-вагон электропоездов; ряды Фурье; current; voltage; random; electric transportation systems